The Evaluation Purposes Visualization - Tarek Azzam; Stewart Donaldson (The Evaluation Center at Western Michigan University, 2024)
Background: The article outlines the development of a visualization that aimed to represent the purpose of different evaluation theories. This visualization used a stream/river metaphor to show the evolution of different purposes (e.g. utilization, knowledge generation, accountability) of evaluation, and also highlighted the historical context that had influenced their development. The visualization shows that the end goal of all these evaluation approaches (i.e. the ocean in which the rivers flow towards) is societal improvement.  Purpose: The article highlights the lessons learned and influences that led to the development of an evaluation theory categorization system. We hope that this would serve as an example (and maybe inspiration) for future efforts that aim to understand how evaluation theories have evolved and developed.  Setting: Not applicable  Intervention: Not applicable  Research Design: Not applicable  Data Collection and Analysis: Not applicable Findings: Not applicable Keywords: Evaluation theory, information visualization, evaluation historical context, organizing framework, theory development.